2019
DOI: 10.1534/g3.119.400508
|View full text |Cite
|
Sign up to set email alerts
|

Joint Use of Genome, Pedigree, and Their Interaction with Environment for Predicting the Performance of Wheat Lines in New Environments

Abstract: Genome-enabled prediction plays an essential role in wheat breeding because it has the potential to increase the rate of genetic gain relative to traditional phenotypic and pedigree-based selection. Since the performance of wheat lines is highly influenced by environmental stimuli, it is important to accurately model the environment and its interaction with genetic factors in prediction models. Arguably, multi-environmental best linear unbiased prediction (BLUP) may deliver better prediction performance than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…In SJ data, pedigree models performed better than marker models while in NS, pedigree models performed similarly to marker models. This result is consistent with previous observations in wheat and sorghum (Juliana et al, 2017;Hunt et al, 2018;Howard et al, 2019). CV0 and CV00 involve more complex prediction situations that span across different environments (years), and in these situations marker information models performed better than pedigree information models.…”
Section: Model Performance Under Different Cross-validation Schemessupporting
confidence: 92%
See 1 more Smart Citation
“…In SJ data, pedigree models performed better than marker models while in NS, pedigree models performed similarly to marker models. This result is consistent with previous observations in wheat and sorghum (Juliana et al, 2017;Hunt et al, 2018;Howard et al, 2019). CV0 and CV00 involve more complex prediction situations that span across different environments (years), and in these situations marker information models performed better than pedigree information models.…”
Section: Model Performance Under Different Cross-validation Schemessupporting
confidence: 92%
“…This scheme is similar to CV0, however, the lines to be predicted have never been observed in the years previously. This scheme applies to breeding situations where most of the materials have not been observed in previous fields but their performance needs to be estimated for the next year (Jarquín et al, 2017;Howard et al, 2019). Here lines that were evaluated only in 2017 but not in any of the previous years were used as validation set while the rest were used as the training set.…”
Section: Assessing Prediction Performance For Different Cross-validatmentioning
confidence: 99%
“…We evaluated the potential of genomic predictions for minimizing the number of replications and lines tested within a site and year and obtained mean PAs of 0.56, 0.5 and 0.42 in Stages 1, 2, and 3 of yield testing respectively, with slight decreases in PAs in the advanced yield trial nurseries that were characterized by fewer and highly selected lines with a narrow GY range. These PAs are within the range or slightly higher than those obtained in previous CV studies for wheat GY: 0.32 (Poland et al, 2012b), 0.22 (Heffner et al, 2011), 0.46-0.63 (Howard et al, 2019), 0.37-0.51 (Juliana et al, 2018b), and 0.44-0.57 (Juliana et al, 2018a).…”
Section: Discussionsupporting
confidence: 68%
“…However, we have also reported only a moderate correlation of 0.64 between the genomic and pedigree relationships and a deviation from the expected relationship of 0.5 between the full-sibs, indicating that there are differences between the genomic and pedigree relationships, part of which can be attributed to pedigree and genotyping errors and the markers not capturing rare allelic differences between lines. While some studies have reported a marginal increase in PAs using combined genomic and pedigree relationships (Crossa et al, 2010;Juliana et al, 2017;Juliana et al, 2018b;Howard et al, 2019), the low value added by genomic relationships in this study suggests that wheat breeding programs with a well-maintained pedigree and family structures like that of CIMMYT in the yield testing stages can just use the available inexpensive pedigree relationship based predictions to minimize the lines in these stages. In addition, breeding programs that have a large number of replications and PAs comparable to the within environment heritabilities can substitute some of the replications with pedigreebased predictions.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation